2011
DOI: 10.1371/journal.pgen.1001354
|View full text |Cite
|
Sign up to set email alerts
|

H3 Lysine 4 Is Acetylated at Active Gene Promoters and Is Regulated by H3 Lysine 4 Methylation

Abstract: Methylation of histone H3 lysine 4 (H3K4me) is an evolutionarily conserved modification whose role in the regulation of gene expression has been extensively studied. In contrast, the function of H3K4 acetylation (H3K4ac) has received little attention because of a lack of tools to separate its function from that of H3K4me. Here we show that, in addition to being methylated, H3K4 is also acetylated in budding yeast. Genetic studies reveal that the histone acetyltransferases (HATs) Gcn5 and Rtt109 contribute to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
148
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(164 citation statements)
references
References 106 publications
12
148
0
1
Order By: Relevance
“…In addition, we speculate that the HU sensitivities of tH2A:H3T3A and tH2A:H3Q5A mutant cells could be due to the defects either in Set1-mediated methylation on H3K4 and/or in binding of effector proteins to methylated H3K4, given the fact that these residues are right next to H3K4. We note a recent report showing that H3K4 can be acetylated in yeast (39). Therefore, it is still possible that H3K4ac may also play a role in HU sensitivity.…”
Section: Double Deletion Of the Histone N-tails Uncovers Unidentifiedmentioning
confidence: 71%
“…In addition, we speculate that the HU sensitivities of tH2A:H3T3A and tH2A:H3Q5A mutant cells could be due to the defects either in Set1-mediated methylation on H3K4 and/or in binding of effector proteins to methylated H3K4, given the fact that these residues are right next to H3K4. We note a recent report showing that H3K4 can be acetylated in yeast (39). Therefore, it is still possible that H3K4ac may also play a role in HU sensitivity.…”
Section: Double Deletion Of the Histone N-tails Uncovers Unidentifiedmentioning
confidence: 71%
“…5D, Lower). H3K4ac has been reported to enrich at active gene promoters just upstream of H3K4me3 (26). Presumably, the observed "TAF3-H3K4ac" interaction might facilitate TAF3 searching for H3K4me3 at the transcription start site by priming the association of TAF3 with promoter chromatin.…”
Section: Resultsmentioning
confidence: 99%
“…H3K4me3 is a marker associated with active transcription, and it has a close relationship with histone acetylation and deacetylation (Eissenberg and Shilatifard, 2010;Guillemette et al, 2011). A previous study has shown that histone H3 is deacetylated globally in the MII oocytes of 3-week-old mice, and the acetylation at all of the lysine residues of histone H3 was undetectable or negligible in the oocytes during meiosis (Kim et al, 2003).…”
Section: Discussionmentioning
confidence: 99%